Excess Properties of Binary Mixture of 2-Nitropropane with p-Xylene at 303.15, 308.15, 313.15 and 318.15 K - Katyal, R.C.; Rattan, V.K.; Singh, Sukhmehar; Kapoor, Seema; Kaur, Jasmeet (Asian Journal of Chemistry, 2010)
The viscosities, densities and speeds of sound for binary mixture of 2-nitropropane with p-xylene at 303.15, 308.15, 313.15, and 318.15 K have been measured over the whole compositional range. The excess thermodynamic properties such as excess volume (VE), deviations in viscosity (Δη) and excess isentropic compressibility (KES ) were calculated.